1990
DOI: 10.1093/bja/64.4.521
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Observations on the Neuromuscular Blocking Action of Org 9426, a New Steroidal Non-Depolarizing Agent

Abstract: The neuromuscular blocking effects of Org 9426, the 2-morpholino, 16-allyl-pyrrolidino derivative of the 3-desacetoxy analogue of vecuronium have been investigated in anaesthetized patients. Based on data from a pilot study, two doses, 250 and 500 micrograms kg-1 (estimated as the ED90 and 2 x ED90, respectively) were chosen. Org 9426 appeared to be six to eight times less potent than vecuronium and showed a faster rate of development of neuromuscular block, with good to excellent intubation conditions within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
54
2
6

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(72 citation statements)
references
References 0 publications
9
54
2
6
Order By: Relevance
“…Based upon previously reported data, 6,7 an assumed interval 25-75% of nine minutes with a SD of 3.3, revealed that a group size of 30 would be required to detect a three-minute difference between the two groups with >0.9 power. As our data displayed normal distribution, paired t test was used for the parametric data and MannWhitney U test was used for nonparametric data analysis.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Based upon previously reported data, 6,7 an assumed interval 25-75% of nine minutes with a SD of 3.3, revealed that a group size of 30 would be required to detect a three-minute difference between the two groups with >0.9 power. As our data displayed normal distribution, paired t test was used for the parametric data and MannWhitney U test was used for nonparametric data analysis.…”
Section: Discussionmentioning
confidence: 93%
“…After T1 baseline stabilization, initial doses of equilasting duration 25% (time from beginning of NMBa administration until 25% T1 recovery) under balanced anesthesia, of either 0.2 mg·kg -1 (3 x ED 95 ) mivacurium expected to last for 21.3 min, 6 or 0.5 mg·kg -1 (1.7 x ED 9 5 ) rocuronium expected to last for 21.2 min, 7 were administered over a period of 30 sec. The trachea was intubated when T1 was suppressed maximally.…”
Section: Anesthesia Protocol and Neuromuscular Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…El rocuronio tiene un perfil muy similar al vecuronio, pero en dosis adecuadas logra un tiempo de inicio de acción muy similar al de la succinilcolina. Fue introducido en clínica en Estados Unidos en 1995 y en Chile en 1996 44 .…”
Section: Aminoesteroidesunclassified
“…The ED9s is [25][26][27][28][29][30] Ixg" kg-t. it has a very slow onset to maximum blockade at subparalysing doses (10-13 min). The duration of clinical anaesthesia following 2 x ED95 doses of 90-120 min is similar to pancuronium as is the recovery index (recovery time from 25 to 75% twitch activity) of 30-50 min.…”
Section: Doxacuriummentioning
confidence: 99%